2015
DOI: 10.1039/c4ra12017e
|View full text |Cite
|
Sign up to set email alerts
|

Non-mercury catalytic acetylene hydrochlorination over Ru catalysts enhanced by carbon nanotubes

Abstract: Highlights• Ru catalysts deposited inside the channels of CNTs show higher catalytic activity.• Ru-in-CNT catalyst exhibited the acetylene conversion of 95.0 % at 170 °C and 10 h.• CNTs with the inner diameter of 3-7 nm can functionalize as an efficient support.Abstract 1 Ru-based catalysts with different deposition sites were prepared using multiwalled carbon 2 nanotubes as the support and RuCl 3 as the precursor, in order to study the effects of multiwalled 3 carbon nanotubes on the catalytic performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…20,21,40 For instance, the amount of Ru 0 was increased, while the amount of Ru 3+ was reduced when the cobalt component was added into RuCl 3 catalyst, which resulted in the better catalytic activity of 1%Ru1Co3/SAC than that of 1%Ru/SAC. 21 Our present DFT results further confirmed that both Ru 0 and Ru 3+ were active species for the reaction of acetylene hydrochlorination.…”
Section: The Effect Of Chloride Coordination Number On the Catalytic mentioning
confidence: 94%
“…20,21,40 For instance, the amount of Ru 0 was increased, while the amount of Ru 3+ was reduced when the cobalt component was added into RuCl 3 catalyst, which resulted in the better catalytic activity of 1%Ru1Co3/SAC than that of 1%Ru/SAC. 21 Our present DFT results further confirmed that both Ru 0 and Ru 3+ were active species for the reaction of acetylene hydrochlorination.…”
Section: The Effect Of Chloride Coordination Number On the Catalytic mentioning
confidence: 94%
“…[19,20] Due to the relatively lower activity and shorter lifetime of non-metallic catalysts, some distance remains from industrialization. As for metal catalysts, a series of metal chlorides, including Pt 4 + , [8,[21][22][23] Pd 2 + , [21,[24][25][26][27] Ru 2 + , [12,[28][29][30][31][32] Cu 2 + , [33,34] Sn 2 + , [35] have been explored as potential Hg-free catalysts, but Au-based catalysts possessing a higher standard reduction potential are considered as the most promising replacement. [4,[36][37][38][39] The coking deposition and the agglomeration or the reduction of active species are the main reasons for the deactivation of Au-based catalyst, which have been briefly introduced in the previous literatures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the group also proposed that an Ru-based catalyst may be another promising candidate [20]. Theoretical and experimental studies on the hydrochlorination of acetylene using Ru-based catalysts have also been carried out previously [21][22][23][24][25][26]. Furthermore, Pd-based catalysts have been extensively studied in the past.…”
Section: Introductionmentioning
confidence: 99%